Vestibular Migraine - Lempert, Thomas (Seminars in Neurology, 2013)
Vestibular migraine presents with attacks of spontaneous or positional vertigo, head motion-induced vertigo, and visual vertigo lasting 5 minutes to 3 days. The recent classification of vestibular migraine, jointly proposed by the Bárány Society and the International Headache Society, allows identification of vestibular migraine and probable vestibular migraine based on explicit criteria. The diagnosis is based on symptom type, severity and duration, a history of migraine, temporal association of migraine symptoms with vertigo attacks, and exclusion of other causes. Because headache is often absent during acute attacks, other migraine features such as photophobia or auras have to be specifically inquired about. During acute attacks, one may find central spontaneous or positional nystagmus, and less commonly, unilateral vestibular hypofunction. In the symptom-free interval, vestibular testing adds little to the diagnosis as findings are mostly minor and nonspecific. The pathophysiology of vestibular migraine is unknown, but several mechanisms link the trigeminal system, which is activated during migraine attacks, and the vestibular system. Treatment includes antiemetics for severe acute attacks, pharmacological migraine prophylaxis, and lifestyle changes.
Keywords: migraine; vestibular; vertigo; dizziness